Mandatory incident reporting through legislative framework: Towards enhancing patient safety culture in healthcare settings - Jahn Kassim, Puteri Nemie (Journal of Humanities, Language, Culture and Business (HLCB), 2017)
Incident Reporting is the cornerstone for improving patient safety as it provides valuable insights on the events leading to the death and injuries of patients in healthcare settings. The availability of such report would enable healthcare providers to take the necessary steps to prevent similar incidents from occurring in the future. Further, an incident report would also be able to identify potential lawsuits and deviations from standard operating procedures. Nevertheless, as incident reports may be open to discovery during litigation process, healthcare providers tend to refrain from giving an honest and accurate account of what has transpired during the incident fearing that they may be reprimanded and punished by the court of law. Therefore, in having a proper legislative framework that mandates incident reporting with provisions that state clearly rules on confidentiality accompanied by regulations on sanctions-free reporting would ultimately encourage healthcare providers to actively report under an environment that is open, fair and non-punitive. Various jurisdictions around the globe such as the United States, Japan and Denmark have employed legislation to introduce a variety of incident reporting systems suited to their local climate. This may provide valuable lessons to countries who wish to introduce or improve their incident reporting systems in ensuring that the occurrence of adverse events are being documented, discussed and prevented. Despite the fallibility inherent to health care delivery, the occurrence of adverse events can be reduced through a commitment of quality improvement in fostering a just culture of safety in the healthcare setting.